Penegakan Hukum Terhadap Tindak Pidana Ringan Dalam Mewujudkan Restorative Justice (Studi Kasus di Kota Jambi) - Effendi, Ipal Gusti; Sahabuddin, S; Alamsyah, Bunyamin (Legalitas: Jurnal Hukum, 2024)
Minor crimes are a category of legal violations that are considered not too serious in the Indonesian criminal justice system. However, their handling remains an important concern to maintain public order and security. Minor crimes generally include violations such as minor insults, minor theft, and minor damage to property. In handling minor crimes, the restorative justice approach has emerged as a promising alternative. This approach aims to restore the situation and resolve conflicts through dialogue and recovery efforts involving all parties, including victims, perpetrators, and the community. However, the implementation of restorative justice in handling minor crimes still faces various challenges and unclear legal norms that need to be addressed. This study aims to analyze the application of restorative justice in law enforcement against minor crimes in Jambi City,